Political violence, democracy and human rights (2016)
Colombia has been characterized through its political history to be bipartisan;  the desire of power has bled the country long ago, and contentions have shown the inequality and social injustice. The Governing body forgets the spirit behind representative democracy, bringing humanity to this minimum expression andignoring human rights. The Government seems to be the most repressive of any kind of movement arising within a society to make its own demands, awakening consciences and calling for a change in favor of the disadvantaged majority. The State is no longer conceived as a democratic apparatus and acquires theconnotation of political apparatus, used to manipulate and exclude with the arrangement of a few holders of power which is legitimated only through a day of voting that does not reflect the popular desire, but the maneuvers that can achieve the inequitable distribution of wealth.